2019
DOI: 10.18632/oncotarget.26915
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DUSP6 sensitizes ovarian cancer cells to chemotherapeutic agents via regulation of ERK signaling response genes

Abstract: Dual specificity phosphatase 6 (DUSP6) is a protein phosphatase that deactivates extracellular-signal-regulated kinase (ERK). Since the ovarian cancer biomarker human epididymis protein 4 (HE4) interacts with the ERK pathway, we sought to determine the relationship between DUSP6 and HE4 and elucidate DUSP6's role in epithelial ovarian cancer (EOC). Viability assays revealed a significant decrease in cell viability with pharmacological inhibition of DUSP6 using (E/Z)-BCI hydrochloride in ovarian cancer cells tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 48 publications
1
31
0
1
Order By: Relevance
“…In recent years, a growing number of investigations have gradually found that HE4 promotes cell proliferation, adhesion, invasion, migration, and chemoresistance in ovarian cancer [20][21][22][23][24][25][26][42][43][44][45][46][47]. It was found that HE4 overexpression or rHE4 treatment in EOC cells resulted in upregulation of many transcripts coding for extracellular matrix proteins, including LAMC2, LAMB3, SERPINB2 and GREM1; moreover, in cells overexpressing HE4 or exposed to rHE4 in culture medium, the protein levels of LAMC2 and LAMB3 were continously increased, and in the presence of bronectin, the focal adhesions were elevated in cells treated with rHE4 [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, a growing number of investigations have gradually found that HE4 promotes cell proliferation, adhesion, invasion, migration, and chemoresistance in ovarian cancer [20][21][22][23][24][25][26][42][43][44][45][46][47]. It was found that HE4 overexpression or rHE4 treatment in EOC cells resulted in upregulation of many transcripts coding for extracellular matrix proteins, including LAMC2, LAMB3, SERPINB2 and GREM1; moreover, in cells overexpressing HE4 or exposed to rHE4 in culture medium, the protein levels of LAMC2 and LAMB3 were continously increased, and in the presence of bronectin, the focal adhesions were elevated in cells treated with rHE4 [22].…”
Section: Discussionmentioning
confidence: 99%
“…It was known that ovarian cancer participates in evading immunosurveillance and orchestrating a suppressive immune microenvironment, a series of studies by James NE, et al [23,44,45] found that, upon exposure of puri ed human peripheral blood mononuclear cells(PBMCs) to HE4, osteopontin (OPN) and DUSP6 appeared as the most inhibited and upregulated genes; the proliferation of human ovarian carcinoma cells in conditioned media from HE4-exposed PBMCs was enhanced, while the effect was attenuated by adding recombinant OPN or OPN-inducible cytokines (IL-12 and IFN-γ); HE4 can compromise both OPN-mediated T cell activation [44] and cytotoxic CD8 + /CD56 + cells through upregulation of self-produced DUSP6 [45], thus promoting the tumorigenesis of ovarian cancer [23,44,45,48]. Other researchers found that HE4 promotes carcinogenesis of ovarian cancer by combining with histone deacetylase 3 (HDAC3) to activate PI3K/AKT pathway [46], and that HE4 knockdown suppresses the invasive cell growth and malignant progress of ovarian cancer by inhibiting JAK/STAT3 pathway [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, HE4 may regulate the mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase/AKT signal transduction (PI3K/AKT) pathways to exert tumor-suppressive effects in vitro [18,19]. Recently, studies have been carried out to investigate the association between HE4 and tumorigenesis as well as chemotherapeutic resistance in EOC; however, these have shown inconsistent results [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%